Collaboration between Child and Adolescent Psychiatry and Child Welfare for Adolescent Girls with Multiple and Complex Needs: An Evaluation by Adolescents, (Step)Parents, and Professionals. Issue 3 (3rd July 2019) - Van den Steene, Helena; van West, Dirk; Glazemakers, Inge
ABSTRACT: Collaboration is put forward as a promising strategy for optimizing care delivery for the most vulnerable populations. The objective of this research was to explore how adolescents, (step)parents and professionals evaluate an intensive collaboration between a child welfare residential center and a child and adolescent psychiatric facility, aiming to optimize care delivery for adolescent girls with multiple and complex needs. This was done using in-depth interviews with nine adolescents and twelve (step)parents, along with focus groups with 44 professionals. Several benefits were identified: (1) care delivery is better tailored to meet individual needs; (2) access to mental health services and therapy implementation and follow-up are ameliorated; (3) focus on integration into society as well as on psychiatric support; (4) capacity and efficiency of care delivery is enhanced. Pitfalls were also mentioned: (1) preserving agency of clients; (2) maintaining the identity of the collaborating partners and openness to professionals outside the collaboration; (3) safeguarding continuity of care; (4) supporting individual professionals and teams. Findings illustrate the potential of collaboration in working with adolescents with multiple and complex needs. They highlight the importance of keeping the needs of adolescents and families as a main focus, while also being attentive to professionals' needs.